A micro-pressure sensor-based analytic platform and its application in thrombin quantification. Issue 19 (7th October 2015) - Yang, Weiqiang; Li, Rongjie; Wang, Qingping; Wei, Qiaohua; Fu, Caili; Lin, Zhenyu; Chen, Guonan
<x xml:space="preserve">Abstract</x> A commercially available micro-pressure sensor was employed to fabricate an analytic platform for detecting biomedical targets based on the fact that hydrogen peroxide can be decomposed by catalase to produce oxygen, which reinforces the pressure in a closed container.